1.8 Å resolution crystal structure of the carbapenem intrinsic resistance protein CarF. Issue 7 (1st July 2017) - Tichy, Evelyn M.; Hardwick, Steven W.; Luisi, Ben F.; Salmond, George P. C.
Abstract : The crystal structure of the carbapenem‐resistance protein CarF has been determined at 1.8 Å resolution. CarF confers partial intrinsic resistance to the naturally occurring antibiotic 1‐carbapen‐2‐em‐3‐carboxylic acid. Abstract : The natural production of the β‐lactam antibiotic carbapenem in bacteria involves a group of enzymes that form a synthetic pathway as well as proteins that protect the cell from self‐intoxification by the products. Here, the crystal structure of CarF, one of the two proteins that confer resistance to synthesis of the antibiotic in the host organism, is reported. The CarF fold places it within a widely occurring structural family, indicating an ancient structural origin from which the resistance function has been derived.